ANTHROPOMORPHIC CHARACTERS IN KAZAKH PROSE (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
This article presents theoretical data on the concept and term of narratology, as well as scientific and methodological analyses related to anthropomorphic characters. Systematic information is provided about narrative methods, and the issue of narratology is discussed. The research article systematically analyzes the narrative skills of various writers using interpretive, structural, semiotic, psychoanalytic, and sociological methods, as well as analyzing excerpts from their works. The study conducted a narratological analysis of the works of Kazakh writers A. Baitursyn, S. Zhunisov, and O. Bokey, as well as the works of foreign writer D. Orwell. The study explores the place and significance of the use of narrative methods, including anthropomorphic characters, and the main ideas presented from a theoretical perspective. The writer's style, their connection with society, and their personal views are analyzed. During the analysis of the works, literary reviews focused on narratology and characters encountered in the works were conducted, and their practical and theoretical value was assessed. Despite the frequent occurrence of such characters in Kazakh literature, there is limited information and research on this concept. The article presents theoretical data on the topic, as well as specific examples from the authors' works, presented to a wide audience.